EDUKASI LATIHAN UNTUK NYERI PUNGGUNG BAWAH PADA LANSIA DI RW 17 POSLANSIA MOJOSONGO SOLO - Wahyu Tri Setyo; Arif Pristanto; Charisa, Anis Dwi (Yayasan Sagita Akademia Maju, 2024)
Reduced functional ability followed by decreased physical activity has a relationship with age and gender. men and women are at the same risk, ranging from reduced muscle strength to endurance. One disorder that is a common health problem in the world and affects almost the entire elderly population is low back pain. Low back pain is pain felt in the lower back area, not a disease or diagnosis for a disease but is a term for pain felt in the affected body area with various variations in the duration of pain. The purpose of this counseling activity is to provide knowledge about low back pain and exercise education to reduce pain intensity. The activity method used is counseling using leaflets with low back pain material and exercise education. The main targets were members and cadres of the elderly posyandu in RW 17 Mojosongo Solo. The result of this counseling is an increase in public understanding and knowledge about low back pain and exercises to reduce this pain. This proves that the counseling method using leaflets is quite effective. It can be seen from the results of the pre-test and post-test participants who showed an average increase of 45%.